IMPLEMENTASI PROGRAM GERAKAN LITERASI SEKOLAH TAHAP PEMBIASAAN DALAM MENGATASI KURANGNYA MINAT BACA SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VII D DI SMP NEGERI 3 SAMBAS TAHUN PELAJARAN 2023-2024 - Halija Halija; Nuraini Nuraini; Asyruni Multahada (CV. ADIBA AISHA AMIRA, 2024)
This research aim to find out and the obtain information about: first, Implementation of the School Literacy Movement program at the habituation stage in overcoming the lack of students' interest in reading in Islamic religious education subjects for class VII at SMPN 3 Sambas in the 2023-2024 Academic Year; second Supporting and inhibiting factors of the School Literacy Movement program at the habituation stage in overcoming the lack of interest in reading for students in Islamic Religious Education subjects for class VII D at SMP Negeri 3 Sambas in the 2023-2024 academic year. This research uses a qualitative approach and a phenomenological research type. Data collection techniques use interviews, observations, and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The results of the research indicate that; The implementation of the school literacy movement program at the habituation stage in overcoming the lack of interest in reading for students in Islamic Religious Education subjects for class VII D at SMP Negeri 3 Sambas in the 2023-2024 academic year, the activities implemented are: 1) getting used to reading for 15 minutes; 2) students have a daily reading journal; 3) good arrangement of literacy facilities; 4) creating a text-rich environment; 5) choosing reading materials; 6) public involvement. Supporting and inhibiting factors of the School Literacy Movement program at the habituation stage in overcoming the lack of interest in reading among students in Islamic Religious Education subjects for class VII D at SMP Negeri 3 Sambas in the 2023-2024 academic year, there are supporting and inhibiting factors, namely: 1) supporting factors, namely government support, availability of Human Resources such as principals and teachers and parents, availability of facilities and infrastructure; 2) inhibiting factors, namely internal factors, such as lack of student awareness of the importance of reading, students are less interested in reading, there are some students who are difficult to manage and external factors, namely the unavailability of the latest reading materials in the near future, short literacy time, the influence of playing gadgets at home.